Effects of E-Module Integrated Problem Based Learning Model of Fluid Material on Student’s Learning Outcomes - Amelia Agustin; Hidayati Hidayati; Fatni Mufit; Renol Afrizon (Jurnal Penelitian Pembelajaran Fisika, 2026)
Improving students’ physics learning outcomes is one of the primary goals of implementing the Independent Curriculum, which emphasizes active, independent, and student-centered learning, However, students learning outcomes on fluid materials remain relatively low because the teaching materials commonly used in schools have not fully facilitated active learning and problem-solving activities. To address this issue, the use of Problem-Based Learning (PBL)-based E-Modules is proposed as an alternative solution to create more meaningful and independent learning experiences. This study aims to analyze the effect of the use of Problem Based Learning (PBL)-based E-Modules on physics learning outcomes of grade XI students of SMA Negeri 14 Padang on fluid materials. The research uses a quasi-experimental method with a Posttest-Only Control Design. The research sample consisted of 71 students divided into experimental classes and control classes. The experimental class uses PBL-based E-Modules, while the control class uses teaching materials commonly used in schools. The research data includes learning outcomes of cognitive, affective, and psychomotor aspects obtained through tests and observation sheets. The results showed that the average learning outcomes of students in cognitive, affective, and psychomotor aspects in the experimental class were higher than in the control class. These findings show that the use of Problem Based Learning-based E-Modules is effective in improving students' physics learning outcomes on fluid materials. The use of PBL-based E-Modules provides benefits in creating more active, meaningful learning, and supports the development of students' knowledge, attitudes, and skills in learning fluid material.